2014
DOI: 10.1111/pcmr.12206
|View full text |Cite
|
Sign up to set email alerts
|

Expression of insulin‐like growth factor‐1 receptor in metastatic uveal melanoma and implications for potential autocrine and paracrine tumor cell growth

Abstract: We investigated the importance of the insulin-like growth factor-1 receptor (IGF-1R) in hepatic metastases of uveal melanoma. The expression pattern of IGF-1R in archival tissue samples of hepatic metastasis from 24 patients was analyzed by immunohistochemistry. All the samples of hepatic metastases stained positive for IGF-1R. To investigate the biological role of IGF-1R on the growth of metastatic uveal melanoma, a long-term cell line obtained from a hepatic metastasis (TJU-UM001) was evaluated. TJU-UM001 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 46 publications
3
39
0
1
Order By: Relevance
“…We determined the effects of clinically relevant, small molecule MEK inhibitors in three genetically characterized cells lines derived from UM metastases: UM001 was established from liver metastasis and harbors a GNAQ Q209P mutation; UM003 was generated from retroperitoneal metastasis and harbors a GNAQ Q209L mutation (25) and UM004 cells were established from orbital metastasis and harbor a GNAQ Q209P mutation (Supp. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We determined the effects of clinically relevant, small molecule MEK inhibitors in three genetically characterized cells lines derived from UM metastases: UM001 was established from liver metastasis and harbors a GNAQ Q209P mutation; UM003 was generated from retroperitoneal metastasis and harbors a GNAQ Q209L mutation (25) and UM004 cells were established from orbital metastasis and harbor a GNAQ Q209P mutation (Supp. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The mutational status of UM001 and UM003 cells were described previously (25). Mutational analysis of GNAQ was performed by Sanger sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…In the selective and rapid growth of uveal melanoma cells in the liver, IGF-1/IGF-1 receptor interactions seem to play a critical role by 'paracrine' stimulation. Yoshida et al [31] investigated the IGF-1 receptor pattern in metastatic liver tissue, and found that the cells proliferated in response to exogenous and endogenous IGF-1. Our study also showed that insulin resistance and basal insulin levels were significantly higher in the uveal melanoma group compared with the controls.…”
Section: Discussionmentioning
confidence: 98%
“…UM001 and UM004 cells were derived from liver and orbital metastases of human UM, respectively; both harbor GNAQ Q209L mutations (20, 24). UM001 cells were cultured in RPMI 1640 medium supplemented with 10% heat-inactivated FBS, 10% non-essential amino acids, 2 mM L-glutamine and 10 mM Hepes buffer.…”
Section: Methodsmentioning
confidence: 99%